1994
DOI: 10.1080/02626669409492751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the water balance for an undeveloped and a suburban catchment

Abstract: Two topographically similar adjacent catchments near Johannesburg, South Africa, one suburban, the other natural grassland, were monitored over a five year period to detect differences in runoff and hydrological balance. A network of raingauges, boreholes, flow gauges and water meters was installed. Evapotranspiration was modelled using observed weather data. Groundwater was estimated from tracer and other borehole tests. Surface runoff from the undeveloped and suburban catchments was 4% and 15% of rainfall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 5 publications
1
22
0
1
Order By: Relevance
“…For example, in Vancouver, British Columbia, lawn irrigation increased evapotranspiration on a 0.21 km 2 suburban area with 40 % impervious cover (Grimmond and Oke 1986). Similar results were observed in a separate study conducted on a 0.75 km 2 suburban catchment with 25 % impervious area in Johannesburg, South Africa (Stephenson 1994). However, further research is required to confirm the applicability of these observations in other urban catchments in water-scarce regions such as SSA.…”
Section: Evapotranspirationsupporting
confidence: 83%
See 2 more Smart Citations
“…For example, in Vancouver, British Columbia, lawn irrigation increased evapotranspiration on a 0.21 km 2 suburban area with 40 % impervious cover (Grimmond and Oke 1986). Similar results were observed in a separate study conducted on a 0.75 km 2 suburban catchment with 25 % impervious area in Johannesburg, South Africa (Stephenson 1994). However, further research is required to confirm the applicability of these observations in other urban catchments in water-scarce regions such as SSA.…”
Section: Evapotranspirationsupporting
confidence: 83%
“…The study further demonstrated that evapotranspiration declined by about 220 mm per year in a catchment with 100 % urbanization. However, on relatively small catchments (<1.0 km 2 ), urbanization has been observed to increase evapotranspiration (Stephenson 1994;Grimmond and Oke 1999). For example, in Vancouver, British Columbia, lawn irrigation increased evapotranspiration on a 0.21 km 2 suburban area with 40 % impervious cover (Grimmond and Oke 1986).…”
Section: Evapotranspirationmentioning
confidence: 98%
See 1 more Smart Citation
“…Typical water balances focus on evaluating the impact of urbanization on the hydrologic system, the provision of traditional water servicing and investigation of attenuation strategies (Stephenson 1994;Grimmond and Oke 1986;Binder et al 1997). The applied methods vary; although the majority involve an accounting of input and output based on average annual or monthly spreadsheet calculations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is possible to say that significant flow regulation leads to a change in FDCs shape, which becomes flatter respect to the natural case, with an attenuation of higher flows (floods) and an increase of low flows [17]. Leopold, in 1968 [18], and Stephenson, in 1994 [19] group in three main categories the impacts on river flow due to anthropic activities: 1) effect on the long-term water balance at the catchment scale (long-term variability); 2) variation from year to year of the statistics of river flow (inter-annual variability); 3) intraannual variation of river flow.…”
Section: Anthropization Effects On River Flow Regimementioning
confidence: 99%